PERLINDUNGAN TERHADAP PENGABAIAN HAK ASUH ANAK AKIBAT PERCERAIAN - Vina Mareta; Muh Jufri Achmad (Gapenas Publisher, 2022)
A child is a person who is under the age of 18, or who has not yet reached the age of 18, including a child in the womb. In a marriage, the child born from the marriage must get his rights without the child asking. This research aims to find out the protection against the neglect of child custody due to divorce. The type of research used in this writing is normative law. The approach used is the statute approach and the conceptual approach. Based on this research, it shows that from the breakup of a marriage, there are legal consequences that follow, one of which is about the custody of the child born from the marriage. Child custody due to divorce falls into the hands of the mother, because the child is still under 12 years old. If the biological father or mother of the child does not want to take care of him, then the most entitled person to obtain custody of the child is the grandmother (the mother of the child's biological mother). If the grandmother (the mother of the child's biological mother) is not present or dies, then the custody of the children is transferred to the grandmother (the mother of the child's biological father). If the grandmother (mother of the child's biological father) is not present or has passed away, then the custody of the child is transferred to the uncle (brother or younger brother of the child's biological mother). If the uncle (brother or younger sister of the child's biological mother) is not present or has passed away, then the custody of the child is transferred to the uncle (brother or younger sister of the child's biological father).